A Case Report Of A Spindle Cell Sarcoma With Ntrk-3 Rearrangement And A Novel Gene Fusion Partner (Ntrk3-Eif2s2). (28th October 2020) - Shalaby, A; Alhussain, A; Al Hmada, Y; Bernieh, A
Abstract: Casestudy: A group of spindle cell tumors with characteristic morphologic features, co-expression of CD34 and S100 and recurrent gene rearrangements in RAF-1, BRAF, and NTRK has recently been described. These tumors were found to be previously labeled as malignant peripheral nerve sheath tumor, infantile fibrosarcoma or unclassified spindle cell sarcoma. We describe a case of a 25-year-old female who presented with a right thigh mass. She underwent an ultrasound-guided biopsy showing a spindle cell tumor with co-expression of CD34 and S100 and subsequently underwent resection of the mass. Gross examination showed a 7.5 cm multi-lobulated, tan-pink, hemorrhagic and fleshy mass. Histologically, the tumor was relatively well-demarcated and consisted of spindle cells with moderate to high cellularity in a patternless architecture. The spindle cells showed moderate to marked pleomorphism, pale amphophilic cytoplasm, ovoid-to-elongated nuclei with vesicular chromatin, and occasional prominent nucleoli. Areas of prominent perivascular and stromal hyalinization were seen. Mitotic activity was brisk with up to 33 mitoses per 10 high power fields. Necrosis representing approximately 5% of the mass was identified. On immunohistochemistry, the tumor cells showed strong and diffuse positivity for CD34 and S100 and were negative for SOX10, broad-spectrum cytokeratin, EMA, SMA, Desmin, STAT6, MUC4, TLE1, and H3K27me3 (retained nuclear expression). EIF2S2-NTRK3 fusion gene was detected using next generation sequencing analysis. Conclusion: A few cases of NTRK3 spindle cell sarcomas, other than classic infantile fibrosarcoma, have been previously reported in the literature with fusion genes involving ETV6, EML4, and STRN, among others. A gene fusion involving NTRK3 and EIF2S2 has not been previously reported. NTRK3-fused sarcomas typically show high-grade morphology and aggressive clinical behavior. Identification of NTRK-fused sarcomas is clinically important, as these advanced tumors are potentially amenable to NTRK inhibition. In our case, patient received adjuvant post-operative radiation therapy and returned with lung metastasis 5 months after surgery.